DOCTORS AS TEACHERS – A HYBRID OF TWO PROFESSIONS: Doctors as Teachers - Mubarik, Azhar (Pakistan Armed Forces Medical Journal, 2009)
INTRODUCTIONThe word ‘doctor’ means physician, and is derived from the Latin “docere” to teach. All doctors have a professional obligation to contribute to the education and training of other doctors, medical students and non-medical healthcare professionals on the team.In the medical profession, teaching expertise has traditionally been assumed to be a part of clinical or scientific expertise. Only since the second half of the 20th century has teaching been acknowledged as a skill in its own right. The presumption that only the proper understanding of a clinical discipline is enough to fulfill a doctor’s educational obligation is no longer acceptable. All doctors require basic training skills. Those who assume more formal teaching responsibilities should be qualified appropriately [1].ATTRIBUTE OF A MEDICAL TEACHERThe role of doctors as teachers is increasingly recognized as a core professional activity that should not be acquired through chance, aptitude or inclination alone. Teaching occurs at all stages of medical career pathway, from formal class-room based learning at undergraduate level through to informal training in the clinical environment. There is, however, no formal requirement or pre-defined route by which doctors can become competent teachers. For example, clinical teachers can often end up in a post through seniority and clinical experience, rather by training and experience in teaching. In such a situation, doctors are under tremendous pressure to meet targets for treating patients and administration, and the responsibility to teach puts another significant demand on their time [2].Doctors who hold senior posts such as consultants, professors, lecturers, tutors and researchers are often seen as role models and it is these individuals who provide teaching to medical students and junior doctors. The attributes of medical role models include a positive attitude towards colleagues, integrity and compassion for patients. The characteristics of excellent role models identified by medical students include personal qualities (eg. interpersonal skills) clinical skills and teaching skills. (eg. ability to explain complex subjects) [3].CHALLENGE TO MEDICAL EDUCATORSAll doctors are obliged to teach, yet there are no mandatory teacher education programmes and doctors have traditionally not received any formal training or teaching qualifications. Although subject expertise is important, it is difficult to assume that because a doctor know a lot about their subject, this will enable them to teach it effectively. Teaching in the medical profession requires a proficient knowledge of how to motivate the learner assess competence, give constructive feed back, teach multiple trainee levels, and the skill to deal with competing demands of patient care, research and education [4].A lack of appropriate teacher education leads to problems with teaching methods. These included a lack of clear objectives, an over-emphasis on factual recall rather than on development of problem solving skills, the use of passive observation rather than active participation of learner, and teaching being pitched at the wrong level. At undergraduate level, the teaching provided by medical academics often focuses on the teacher’s area of research rather than providing a comprehensive over view of the subject. Evidence suggests that clinical teaching can be variable, and un-preductable poorly supervised and assessed, often opportunistic and may approach humiliation and sarcasm.Other challenges to medical educationist are practical difficulties like expansion of student numbers, the development and implementation of integrated medical curricula, and the increasing emphasis on self-directed and problem based learning alter the way in which medicine needs to be taught. Further more the doctor who teach is often poorty rewarded in terms of remuneration and recognition.IMPROVING MEDICAL TEACHINGRecent years have seen a number of encouraging developments including the establishment of medical education department in medical college, the introduction of few medical educational academic posts and the introduction of a variety of teaching courses relevant to medical profession. Doctors are now taking advantage of the increasing range of opportunities to improve their teaching skills. There are a variety of teaching qualifications and specialized teaching courses available to health care professionals. These range from masters programmes to two or three day teaching improvement courses:• Master degrees• Postgraduate diploma• Postgraduate certificate• Work shops (e.g. Teaching the teachers workshop)• Distance learning courseASSESSING TEACHING QUALITYAssessing the quality of teaching in the medical profession is not only essential to identify weaknesses in teaching skill, but also to provide a subjective measure by which teaching involvement can be rewarded. In assessing the quality of teaching it is important that feedback is sought from the individuals being taught.Standards for assessment should be developed, and these could include assessment of [6]:• The clarity of teaching objectives.• The choice of learning methodology to meet the objectives.• The quality of teaching materials (notes, handouts and visual aids)• Qualitative assessments of their performances in lecturing, workshops and clinical training.• The volume and range of teaching undertaken.• The range of assessment techniques used.RECOMMENDATIONS            Improving the delivery of teaching in medicine requires a multi-dimensional approach across the profession at the level of individual doctors, healthcare and academic institutions, training and regulatory bodies, and relevant governmental departments.British medical association gives following recommendation [2]:• All doctors should recognize their professional obligation to teach.• Medical teachers should develop teaching skills that reflect their individual level of teaching involvement and their skills should be regularly consolidated and updated.• Teaching should be recognized as a core professional activity equivalent to research and patient care.• Opportunities to acquire and develop teaching skills should be provided at all levels of the medical profession through a structured training programme that beings at undergraduate level and continues through to senior posts.• The provision of teacher education should be a core component of undergraduate and postgraduate medical curricula.• Doctors should be subject to regular reviews of their teaching responsibilities and the quality of teaching they provide.• Medical education funding should be more transparent• Teaching should be made a top priority by all organizations with strategic and operational responsibility for the education, career progression and development of doctors.• Teaching post with significant, formal responsibilities should be recruited primarily on the basis of teaching expertise.• The educational contribution of doctors should be adequately rewarded.• Inclusive environment should be provided that lead to effective teaching and learning.• Doctors who have particular interest and aptitude for teaching, or who are seen as role models should be encouraged to develop their skills further.• There should be further research into teaching in the medical profession.